Essential oil constituents of the leaves, bark and cones of Juniperus oxycedrus subsp oxycedrus L. from Turkey - Hayta, Sukru; Bagci, Eyup (Soc Botanique France, 2014)
The essential oil composition of the leaves, bark and cones of Juniperus oxycedrus subsp. oxycedrus collected from natural habitats in Bursa (Turkey) were determined by hydrodistillation, in 0.7, 0.9 and 0.7% (weight/weight) yields, respectively. The essential oils were analysed by gas chromatography and gas chromatography/mass spectrometry. A total of 75 compounds have been identified constituting 99.5% in bark, 89.3% in leaves and 97.7% in cones of the essential oils of the taxon. The predominant compounds were alpha-pinene (42.9, 72.8 and 20.9%), beta-pinene (3.8, 10.7 and 8.9%), beta-myrcene (3.9, 5.5 and 21.7%) and limonene (17.8, 1.9 and 3.4%) in the oils from the leaves, bark and cones, respectively. Quantitative and qualitative variations were determined in the essential oil composition of different parts of the studied plant. The high amount of monoterpenes alpha- and beta-pinene, beta-myrcene, limonene and the sesquiterpene germacrene D make the studied taxon a privileged potential source for pharmaceutical, cosmetic and industrial products. The essential oil composition of different parts of Juniper oxycedrus from Bursa (Turkey) confirm the relevance of the medicinal usage of these plant parts.
Keywords: essential oil; gas chromatography/mass spectrometry; Juniperus oxycedrus subsp oxycedrus; beta-myrcene; alpha-pinene